Ampliación del mantenimiento preventivo de grupos electrógenos conservando los criterios de funcionamiento correcto (2023)
This research focuses on the expansion of preventive maintenance of generator sets, ensuring that they are maintained the criteria for correct operation. The groups Generators are devices that generate energy backup power when a power outage occurs the main supply.